1991
DOI: 10.1016/0042-6822(91)90611-e
|View full text |Cite
|
Sign up to set email alerts
|

Expression of measles virus RNA in peripheral blood mononuclear cells of patients with measles, SSPE, and autoimmune diseases

Abstract: ln order to characterize measles virus (MV} infection in peripheral blood mononuclear cells (PBMCs), RNA was isolated from PBMCs after PHA-stimulation for 72 hr of 9 patients with acute measles, 16 patients with subacute sclerosing panencephalitis (SSPE), 13 patients with various autoimmune diseases, and 16 healthy control donors. The RNA obtained was screened for the presence of MV N (nucleocapsid) gene specific transcripts of either positive or negative orientation in a S 1 nuclease protection assay. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…One study using a cloned probe [114] indicated by dot blot the presence of MV RNA in 28 out of 34 SLE patients and not in 29 controls. A study using the more sensitive S1 nuclease protection assay was not able to confirm the presence of MV-specific RNA in the PBMCs of SLE patients [115]. However, to the best of our knowledge, RT/PCR has not yet been applied.…”
Section: Systemic Lupus Erythematosismentioning
confidence: 77%
“…One study using a cloned probe [114] indicated by dot blot the presence of MV RNA in 28 out of 34 SLE patients and not in 29 controls. A study using the more sensitive S1 nuclease protection assay was not able to confirm the presence of MV-specific RNA in the PBMCs of SLE patients [115]. However, to the best of our knowledge, RT/PCR has not yet been applied.…”
Section: Systemic Lupus Erythematosismentioning
confidence: 77%
“…The spontaneous proliferation of mononuclear cells sampled from the peripheral blood of infected individuals occurs just before the rash appears and persists for several weeks (39, 42), providing multiple targets for productive MV infection (131). Nevertheless, MV infects only a small proportion of circulating PBMC in the infected host (49,96,116,135), and the major cell type infected in vivo seems to be in the monocyte/macrophage lineage (29).…”
Section: Proposed Mechanisms Of MV Immunosuppressionmentioning
confidence: 99%
“…The tropism of MV for cells of the lymphocytic and monocytic lineage is well established both in vivo and in vitro (Esolen et al, 1993 ;Schneider-Schaulies et al, 1991 ;Joseph et al, 1975) ; particularly, MV infection interferes with the proliferation and generation of specialized lymphocyte functions in vitro, but not with those already established prior to infection (Galama et al, 1980 ;Yanagi et al, 1992 ;McChesney et al, 1987McChesney et al, , 1988. Detailed analyses revealed that MV infection caused an arrest in the G " phase of the cell cycle in these cells (Yanagi et al, 1992 ;McChesney et al, 1987McChesney et al, , 1988.…”
Section: Introductionmentioning
confidence: 99%